A prospective naturalistic multicenter study on choice of parenteral medication in psychiatric emergency settings in Japan. Issue 3 (24th May 2018) - Hatta, Kotaro; Katayama, Shigemasa; Morikawa, Fumiyoshi; Imai, Atsushi; Fujita, Kiyoshi; Fujita, Aiko; Ishizuka, Takuya; Abe, Takayuki; Sudo, Yasuhiko; Hashimoto, Kijiro; Usui, Chie; Nakamura, Hiroyuki; et al.
Abstract: Aim: To provide information about psychiatric emergency situations in Japan, we examined psychiatrists' preference among parenteral medication since intramuscular (IM)‐olanzapine became available and clinical characteristics in patients given IM‐olanzapine compared to those given other parenteral medication. Methods: We conducted a naturalistic study proceeding over a 1‐year period in 9 psychiatric emergency departments. Results: Among 197 patients, the distribution of IM‐injections (n = 89) was as follows: IM‐olanzapine, 66 patients (74.2%), IM‐levomepromazine, 17 patients (19.1%), IM‐haloperidol, 5 patients (5.6%), and IM‐diazepam, 1 patient (1.1%). The distribution of intravenous (IV)‐injections (n = 108) was as follows: IV‐haloperidol, 78 patients (72.2%), and IV‐benzodiazepines (diazepam, flunitrazepam, or midazolam), 30 patients (27.8%). Advantages of IM‐olanzapine over other parenteral medications in efficacy were found as follows: less frequent needs of an additional injection despite no difference in duration until a patient became cooperative for oral administration, and less frequent needs of restraint after the injection. Furthermore, advantages of IM‐olanzapine over other injections in safety were found as follows: less frequent appearance of extrapyramidal symptoms, no occurrence of ECG abnormality and other serious adverse events except a fall, less frequent needs of an adjunctive anticholinergic drug, and less frequent needs of another kind of drug additionally injected. Conclusions: Olanzapine has rapidly become the first choice of intramuscular medication in psychiatric emergency situations since it became available in Japan, probably due to the advantages in both efficacy and safety. This study reflecting psychiatric emergency practice in Japan may contribute to periodic international comparison of psychiatric emergency practice.